Rethinking, repackaging, and rescuing world trade law in the post-pandemic era - Boklan, Daria; Zhou, Weihuan; Bahri, Amrita (London [England] : Hart Publishing, 2021)
"This book explores the ways to 'rethink', 'repackage' and 'rescue' world trade law in the post-COVID-19 era. Using the COVID-19 pandemic as an important context, the book makes original and critical contributions to the growing debate over a range of emerging challenges and systemic issues that might change the landscape of world trade law in the years to come. The book asks: do these unprecedented times and challenges call for reengineering the world trading system and a further retreat from trade liberalisation? The authors offer a rigorous and insightful analysis of whether and how the existing trade institutions and/or rules, including their latest developments, may provide room to deal with pandemic-induced trade-related issues, sustainable development goals, future crises and other existential threats to the multilateral trading system. The book reinforces the importance of international cooperation and the pressing need to reinvigorate the world trading system. The pandemic has provided a unique opportunity for governments to rebuild the political will needed for such cooperation. One should never let a serious crisis go to waste."--
1. Introduction: Rethinking, Repackaging and Rescuing World Trade Law in the Post-Pandemic Era Weihuan Zhou (UNSW, Australia), Amrita Bahri (ITAM, Mexico) and Daria Boklan (National Research University Higher School of Economics, Russia) Part I - Rethinking World Trade Law and the Pandemic -- 2. An Overview of Trade-Related Measures Taken by WTO Members during the COVID-19 Pandemic and a Few Reflections Thereon Jan Bohanes (Advisory Centre on WTO Law, Switzerland) -- 3. Export Restrictions on Food Commodities during the COVID-19 Crisis: Implications for Food Security and the Role of the WTO Ilaria Espa (University of Lugano, Switzerland) -- 4. Time to Reform the Non-Actionable Subsidy Rules in the WTO: The COVID-19 Subsidies and Beyond Ru Ding (Chinese University of Political Science and Law, China) -- 5. Re-Thinking WTO DSB Jurisdiction in Light of the Pandemic, Climate Change and Other Evolving Threats Alexandra Harrington (Albany Law School, USA) -- 6. The WTO and Brazil's Trade Responses amid the Pandemic: Can Transparency Overcome Populism? Michelle Ratton Sanchez Badin (Getulio Vargas Foundation, Brazil) and Magali Fernandes (Getulio Vargas Foundation, Brazil) Part II - Repackaging World Trade Law and Sustainable Development -- 7. Trade and UN SDGs 2030: The Interplay between Public International Law and Contract Law Lorenza Mola (University of Turin, Italy) and Cristina Poncib (̣University of Turin, Italy) -- 8. Combating Climate Change under the WTO: Exploring the Relevance of Process and Production Methods Daria Boklan (National Research University Higher School of Economics, Russia) -- 9. The EU Green Deal and International Trade Law: Bringing Trade and Sustainability Together Luana Almeida (CLOO Behavioral Insights Unit, Portugal) -- 10. Gender Mainstreaming in Free Trade Agreements: What Have We Achieved, and What More Is Needed for Inclusive Post-Pandemic Recovery? Amrita Bahri (ITAM, Mexico) Part III - Rescuing World Trade Law and Other Fundamental Challenges -- 11. The Current State of Dispute Settlement at the WTO: How Did We Get Here and What Next? Jan Yves Remy (Shridath Ramphal Centre for International Trade Law, Policy and Services, Barbados) -- 12. Precedent in the MPIA: What Role for Consistency and Predictability? Mariana Clara de Andrade (University of Milano-Bicocca, Italy) -- 13. Is the Phase One Deal the Emergence of a 'New Generation' of Bilateral Trade Agreements that Challenge the WTO? Maria Manuela Moccero (Ministry of Foreign Affairs, Argentina) -- 14. China's Response to the 'Market-Oriented Conditions' Proposal for WTO Reform and its Implications in the Era of (Post-) COVID-19 Luyao Che (Chinese University of Political Science and Law, China) -- 15. Winning Strategy or Own Goal? Reflections on the United States Exiting the Trans-Pacific Partnership Meredith Kolsky Lewis (University at Buffalo, USA)
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Foreign trade regulation; Foreign trade regulation -- International cooperation; COVID-19 Pandemic, 2020-; Electronic books